Efficacy of luteal estrogen administration and an early follicular Gonadotropin-releasing hormone antagonist priming protocol in poor responders undergoing fertilization - Hwajeong Lee; Hyun Joung Choi; Kwang Moon Yang; Min Jung Kim; Sun Hwa Cha; Hyun Jeong Yi (Korean Society of Obstetrics and Gynecology, 2018)
ObjectivesWe investigated whether luteal estrogen administration and an early follicular Gonadotropin-releasing hormone antagonist (E/G-ant) priming protocol improves clinical outcomes in poor responders to controlled ovarian stimulation for in vitro fertilization (IVF)-embryo transfer, and identified underlying mechanisms.MethodsThis restrospective study consisted of 65 poor responders who underwent the E/G-ant priming protocol. Sixty-four other poor responders undergoing conventional protocols without pretreatment were included as the control group. Clinical outcomes were compared between 2 groups.ResultsThe E/G-ant priming protocol group exhibited improvements over the control group in terms of the number of retrieved oocytes (3.58±2.24 vs. 1.70±1.45; P=0.000), mature oocytes (2.68±2.11 vs. 1.65±1.23; P=0.000), fertilized oocytes (2.25±1.74 vs. 1.32±1.26; P=0.001), good embryos (1.62±0.91 vs. 1.14±0.90, P=0.021). Day 3 follicle-stimulating hormone (FSH; 8.40±4.84 vs. 16.39±13.56; P=0.000) and pre-ovulation progesterone levels (0.67 vs. 1.28 ng/mL; P=0.016) were significantly higher in the control group than in the E/G-ant priming group. The overall rate of positive human chorionic gonadotropin tests was higher in the E/G-ant priming group than in the control group (32.3% vs.16.1%; P=0.039). Also, clinical pregnancy rate (26.2% vs. 12.5%; P=0.048) and the rate of live births (23.1% vs. 7.1%; P=0.023) were significantly higher in the E/G-ant priming group than in the control group.ConclusionThe E/G-ant priming protocol would lead to promising results in poor responders to IVF by suppressing endogenous FSH and by preventing premature luteinization.